Vagal Paraganglioma Presenting as a Neck Mass Associated with Cough on Palpation - Richard Heyes; Nizar Taki; Miriam A. O’Leary (Case Reports in Otolaryngology)
A 70-year-old female presented with a neck mass and sporadic dry cough, often leading to fits of coughing severe enough to cause vomiting. The patient reported that touching the mass triggered the cough. On examination, a 2.5 cm right-sided level two neck mass deep to the sternocleidomastoid was present. Palpation of the mass immediately triggered coughing. Cross-sectional imaging proposed vagal paraganglioma as the chief differential, which was confirmed following surgical excision. The patient reported complete resolution of her severe dry cough after surgery. Vagal paragangliomas are rare neuroendocrine tumors arising from the neural crest-derived paraganglionic tissue surrounding the vagus nerve, typically presenting as a neck mass associated with hoarseness or pulsatile tinnitus. To the best of our knowledge this is a unique description in the English literature. This case is presented to aid physicians should they encounter a neck mass associated with cough. Vagal paraganglioma, although rare, should be part of the differential in such a presentation.